1990
DOI: 10.1177/105345129002500301
|View full text |Cite
|
Sign up to set email alerts
|

Prereferral Intervention Through Teacher Consultation

Abstract: A consultation process and intervention procedures are described for teachers and support staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The team may refine the suggested interventions to continue working with the child in the general education setting, discontinue the process if the problem leading to referral is solved, or refer the child to special education for assessment to determine whether she is qualified for special education services. Fuchs, Fuchs, and Gilman ( 1990) identified four key features of the prereferral intervention process. First, it reflects the Least Restrictive Environment (LRE) mandate of IDEA 1997 (originally specified in P. L. 94-142).…”
mentioning
confidence: 99%
“…The team may refine the suggested interventions to continue working with the child in the general education setting, discontinue the process if the problem leading to referral is solved, or refer the child to special education for assessment to determine whether she is qualified for special education services. Fuchs, Fuchs, and Gilman ( 1990) identified four key features of the prereferral intervention process. First, it reflects the Least Restrictive Environment (LRE) mandate of IDEA 1997 (originally specified in P. L. 94-142).…”
mentioning
confidence: 99%
“…As noted in the introduction, there is a paucity of technical assistance models that are demonstrably effective. Of those that have empirical support (e.g., Fuchs et al, 1990aFuchs et al, , 1990bHendrickson et al, 1993;Peck et al, 1989), a common characteristic is a multicomponent intervention combining didactic instruction (e.g., workshops) and onsite training and performance feedback for educational personnel. These features differ from the traditional technical assistance models used by LEAs that are based primarily on workshop or inservice training (e.g., Briggs et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that technical assistance combining workshops and onsite consultation results in changes in school teaching practices (Fuchs, Fuchs, & Bahr, 1990a;Fuchs et al, 1990b;Hendrickson, Gardner, Kaiser, & Riley, 1993;Peck, Killen, & Baumgart, 1989). Related research has also shown that providing performance feedback can be an important component in technical assistance provision to educators (Fantuzzo & Atkins, 1992;Noell & Witt, 1999;Northup et al, 1994;Wolery, Anthoy, & Snyder, 1997).…”
mentioning
confidence: 99%
“…Child study teams, a prereferral strategy that was popularized in U.S. schools in the early 1990s (e.g., Fuchs et al, 1990;Ingalls & Hammond, 1996), typically consist of a group of general educators, special educators, and administrators from a specific school who meet to discuss individual student cases. Although child study teams offer many advantages (Rock & Zigmond, 2001), if they are not part of wider systems of change within a school, they can become simply another stage of special education referral.…”
Section: The Child Study Processmentioning
confidence: 99%